User authentication scheme with anonymity, unlinkability and untrackability for global mobility networks. Issue 11 (11th March 2013) - Lee, Tian‐Fu
ABSTRACT: User authentication procedures are essential for global mobility networks and enable a mobile user to communicate securely with other users. Chang et al . recently presented an efficient authentication scheme with user anonymity in roaming environments. The authentication scheme of Chang et al . used low‐cost functions and was most suitable for battery‐powered mobile environments. However, Youn et al . pointed out that their authentication scheme cannot ensure user anonymity and resist known session key and side channel attacks. This study will demonstrate that the scheme of Chang et al . cannot resist impersonation attacks and violates session key security. In addition, this study present a secure and efficient authentication scheme based on the scheme of Chang et al . The proposed scheme not only avoids the weaknesses of the authentication scheme of Chang et al . but also ensures data unlinkability and users untrackabilty. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This investigation demonstrates that the scheme of Chang et al . cannot resist impersonation attacks and violates session key security. In addition, a secure and efficient authentication scheme based on the scheme of Chang et al . is proposed. The proposed scheme avoids the weaknesses of the authentication scheme of Chang et al . and ensures data unlinkability and users untrackability.